1996
DOI: 10.1099/13500872-142-12-3505
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and antigenic cross-reactivity of the transferrin-binding proteins of Haemophilus influenzae, Actinobacillus pleuropneumoniae and Neisseria meningitidis

Abstract: Haemophilus influenzae acquires iron from the iron-transporting glycoprotein transferrin via a receptor-mediated process. This involves two outer-membrane transferrin-binding proteins (Tbps) termed T b p l and Tbp2 which show considerable preference for the human form of transferrin. Since the Tbps are attracting considerable attention as potential vaccine components, we used transferrin affinity chromatography to examine their conservation amongst 28 H. influenzae type b strains belonging to different outer-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(26 reference statements)
2
12
0
Order By: Relevance
“…[148,150]. Sera from healthy adults recognize Tbp1 and Tbp2, arguing that these proteins are expressed in vivo [150,151]. Consistent with this observation, as assessed by RT-PCR, both proteins are expressed during acute otitis media [152].…”
Section: Iron and Heme Acquisitionsupporting
confidence: 58%
See 1 more Smart Citation
“…[148,150]. Sera from healthy adults recognize Tbp1 and Tbp2, arguing that these proteins are expressed in vivo [150,151]. Consistent with this observation, as assessed by RT-PCR, both proteins are expressed during acute otitis media [152].…”
Section: Iron and Heme Acquisitionsupporting
confidence: 58%
“…Tbp1 is an integral outer membrane protein, while Tbp2 appears to be anchored in the outer membrane via a lipid moiety [149]. Sera from healthy adults recognize Tbp1 and Tbp2, arguing that these proteins are expressed in vivo [150,151]. [148,150].…”
Section: Iron and Heme Acquisitionmentioning
confidence: 99%
“…The surface accessibility and role in virulence of the Hb and transferrin receptors made them early candidates for vaccine development (Afonina et al, 2006; Cornelissen, 2003). The transferrin and Hb receptors of Haemophilus influenza, Neisseria meningitidis , and Neisseria gonorrhoeae were the early focus of such studies (Holland et al, 1996; Lewis et al, 1999; Richardson & Stojiljkovic, 1999; Stevenson, Williams, & Griffiths, 1992; Webb & Cripps, 1999). However, a potential drawback has been the high level of redundancy and phase variation in the transferrin and heme uptake systems (Ekins, Bahrami, Sijercic, Maret, & Niven, 2004; Richardson & Stojiljkovic, 1999, 2001).…”
Section: Heme Uptake and Utilization In Antimicrobial Drug Developmentioning
confidence: 99%
“…The TbpA proteins are generally highly conserved within a species, while the TbpB proteins tend to be more variable. For N. meningitidis, it was found that the TbpB proteins could be separated into two families based on sequence and antigenicity (28); however, there are common antigenic domains in the TbpB proteins from N. meningitidis, N. gonorrhoeae, H. influenzae, and A. pleuropneumoniae (17,33). Furthermore, TbpBs from N. meningitidis, H. influenzae, and A. pleuropneumoniae have been demonstrated to be protective antigens in various animal challenge models (1,21,22,29).…”
mentioning
confidence: 99%